Identificação genética no processo penal : verdade, ciência e processo na sociedade complexa - Felix, Yuri (2014)
The present study was developed in the area of concentration and Criminal Violence System in research-Criminal Legal Systems Contemporary line, aims to analyze the use of DNA in the criminal justice process. Divide the approach of the object in three parts in terms of truth, science and process, discussing points as the game rules in criminal proceedings, the right to defense, characteristic points of proportionality, called the real truth and its related technology genetic / scientific truth and deeper details of the characteristics, structure and function of DNA. Also, addressing himself particulars relating bodily interventions, the evaluation of scientific evidence and the free-motivated conviction of the judge. Finally, treated of aspects involving the constitutionality and the proportionality of Law n° 12.654/12 - Law of criminal genetic identification - but also, its vicissitudes and gaps, pointing to the consequences that this legislative product can lead this historic moment Brazilian criminal procedure.